Full‐state discrete‐time model‐based stability analysis and parameter design of dual active bridge converter in energy storage system. Issue 13 (2nd June 2022) - Xiao, Zhongxiu; Lei, Wanjun; Xiang, Zhangwei; Yin, Yilin; Wang, Wenhua
Abstract: The dual active bridge (DAB) converter plays a crucial role in energy storage system application of DC microgrid. In such a cascade system, maintaining its stability is imperative for reliable operation of the DAB converter under constant current, constant power, and constant voltage charging mode. Firstly, the accurate discrete‐time models considering parasitic resistances are applied for three charging modes to reveal the system dynamic characteristics. The discrete‐time small‐signal models for different operation modes are developed further which gives guidance in the controller's parameters design. Secondly, the comprehensive and systematic analysis of all the possible unstable phenomena for three charging modes are conducted according to the discrete‐time model. Finally, the underlying mechanisms are revealed by analyzing the relationships among the state variables, the Floquet multipliers, and system parameters. It is demonstrated that the inductor and output capacitor of the DAB converter, the DC bus voltage, the equivalent series resistance of the battery, and the proportional constant can influence the system stability under all charging modes greatly. Hence, the stability‐oriented parameter design process is given which can provide the guidance in practical. The theoretical analysis under these three types operating modes is verified by simulations and experimental results.